Gelsolin Restores Aβ-Induced Alterations in Choroid Plexus Epithelium - Vargas, Teo (Hindawi Publishing Corporation, 2010)
Histologically, Alzheimer's disease (AD) is characterized by senile plaques and cerebrovascular amyloid deposits. In previous studies we demonstrated that in AD patients, amyloid-β (Aβ) peptide also accumulates in choroid plexus, and that this process is associated with mitochondrial dysfunction and epithelial cell death. However, the molecular mechanisms underlying Aβ accumulation at the choroid plexus epithelium remain unclear. Aβ clearance, from the brain to the blood, involves Aβ carrier proteins that bind to megalin, including gelsolin, a protein produced specifically by the choroid plexus epithelial cells. In this study, we show that treatment with gelsolin reduces Aβ-induced cytoskeletal disruption of blood-cerebrospinal fluid (CSF) barrier at the choroid plexus. Additionally, our results demonstrate that gelsolin plays an important role in decreasing Aβ-induced cytotoxicity by inhibiting nitric oxide production and apoptotic mitochondrial changes. Taken together, these findings make gelsolin an appealing tool for the prophylactic treatment of AD.